2018
DOI: 10.1111/ecc.12976
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity, longitudinal trends and predictors of acute and chronic oxaliplatin‐induced peripheral neuropathy in Taiwanese patients with colorectal cancer

Abstract: The purpose of this study was to evaluate the longitudinal incidence, severity, pattern of changes or predictors of oxaliplatin‐induced peripheral neuropathy (OXAIPN) in Taiwanese patients with colorectal cancer. A longitudinal repeated measures study design was employed, and 77 participants were recruited from the colorectal and oncology departments of two teaching medical centres in Taiwan. Physical examinations were performed, and self‐reports regarding adverse impacts of OXAIPN and quality of life were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 39 publications
0
23
0
6
Order By: Relevance
“…This remarkable variability still needs to be fully explained because different studies have failed to unequivocally indicate which might be the risk factors or the predictors for the final neurological outcome in each patient. Apart from cumulative dose, which is clearly associated with more severe neurotoxicity, several other apparently obvious risk factors for peripheral nerve damage failed to demonstrate consistent results in different studies . This is the case for diabetes, age, previous chemotherapy, while other risk factors less commonly associated to increased incidence of peripheral neuropathies, such as body mass index and smoking, were occasionally reported.…”
Section: Risk Factors and Pharmacogeneticsmentioning
confidence: 90%
“…This remarkable variability still needs to be fully explained because different studies have failed to unequivocally indicate which might be the risk factors or the predictors for the final neurological outcome in each patient. Apart from cumulative dose, which is clearly associated with more severe neurotoxicity, several other apparently obvious risk factors for peripheral nerve damage failed to demonstrate consistent results in different studies . This is the case for diabetes, age, previous chemotherapy, while other risk factors less commonly associated to increased incidence of peripheral neuropathies, such as body mass index and smoking, were occasionally reported.…”
Section: Risk Factors and Pharmacogeneticsmentioning
confidence: 90%
“…The summed scores of each subscale and the overall CIPN scale are converted into standardized scores ranging from 0 to 100, with higher scores representing more CIPN–related symptom distress. The scale was translated into Chinese, and previous cancer-related studies reported satisfactory psychometric properties for the EORTC QLQ–CIPN20 [ 18 , 21 ]. The EORTC QLQ–CIPN20 has been demonstrated to be reliable in a cancer-related study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have explored these issues, most research has focused on patients with colorectal cancer [ 18 , 19 , 20 ], breast cancer [ 21 ], or those in Western countries [ 22 , 23 , 24 ]; or on other chemotherapy regimens such as taxane [ 22 , 23 ], paclitaxel [ 23 , 24 ], or carboplatin [ 23 , 24 ]. Clinical observation indicates that LC patients treated with platinum-based regimens report CIPN-related symptoms that affect daily function and QoL, and insufficient attention has been devoted to this important topic.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of previous research showing that numbness/tingling was associated with functional impairment and reduced QoL, [68,154,216,217] which interfered with daily activities [102] and reduced enjoyment of life. [218] Given the lack of effective treatment for numbness/tingling, it is important to assess this symptom and its severity systematically and to modify the chemotherapy dose when needed (dose limitation). [208,219]…”
Section: Symptom Burden and Qol And Associated Factorsmentioning
confidence: 99%